Earthly Pages : The Poetry of Don Domanski - Domanski, Don (Book collections on Project MUSE., 2007)
With The Cape Breton Book of the Dead, Don Domanski emerged as a remarkable new voice in Canadian poetry, combining formal conciseness with broad cosmic allusions, constant surprise with brooding atmospherics, and innovative syntax with delicate phrasings. In subsequent collections, Domanski's poetry has deepened and expanded, with longer lines and more complex structures that journey into the far reaches of metaphor. Now, with Earthly Pages: The Poetry of Don Domanski, the long-awaited first selection from his books, readers have a chance to experience the full range of his work in one volume. Editor Brian Bartlett, in his introduction, "The Trees are Full of Rings," discusses Domanski's engagement with nature and the transformative power of his metaphors; his poetic bestiary amd mythical underpinnings; and his kinship to poets like Stevens, Whitman, and Rumi. Like these poets, Domanski is drawn to borderlands between the physical and the spiritual, the unconscious and the conscious. His poetry finds a home for demons and angels, spiders and wolve and for kitchens and back alleys, forests and stars. In language both fluent and hypnotic, Domanski maintains an awareness of both the magnitudes and the minutiae that live beyond language. In "Flying Over Language," an essay written specifically for this volume, the poet explains that for him metaphor is one way to suggest the wealth of being that poetry can only point toward